Kandungan Nutrisi Maggot yang Diaplikasikan pada Budidaya Ikan Lele (Clarias sp) - Edi Alazhar; Putri Ramdhani; Maya Romanti Tampubolon (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Catfish are a fish with a high protein content and are popular with the public. However, their food conversion ratio is relatively high because they are omnivorous. Therefore, supplementary feed is needed to reduce production costs. One type of supplementary feed that can be used is natural or live feed. According to Anggitasari, Syofan, and Djunadi (2016), BSF maggots can be used as livestock feed and can reduce feed prices. Therefore, it is necessary to analyze maggots as a supplementary food for catfish. Observations of catfish fed fresh maggots for 14 days showed no mortality, and the fish's response time was around 10-13 seconds.